Scurvy in children: Down but not out - Sukhjot Kaur; Jatinder Singh Goraya (Wolters Kluwer Medknow Publications, 2021)
Background: Scurvy, a common disease of the past, has become rare in the modern era. Because of lack of awareness regarding its clinical and radiological manifestations, diagnosis of scurvy is often missed or delayed resulting in unnecessary and potentially harmful diagnostic and therapeutic interventions. Dermatological manifestations are a very important component of the clinical picture and can suggest the diagnosis to the unsuspecting physicians. The objectives were to describe the clinical presentation of scurvy in children in the modern era and to highlight its dermatological manifestations. Methods: This was a retrospective chart review of children diagnosed with scurvy over a period of 10 years at a tertiary care hospital. Results: Eleven children, 6 girls and 5 boys, aged from 21 months to 16 years with scurvy were identified. All the children had an underlying disorder that predisposed them to scurvy, with cerebral palsy in 10 and autism spectrum disorder with celiac disease in one child. All had presented with musculoskeletal complaints of irritability, limb pain, painful restriction of movements, and in some cases, swelling of the affected limb. Dermatological signs consisting of various combinations of perifollicular hyperkeratosis and hemorrhages, petechiae, ecchymosis, corkscrew hair, and bleeding gums were present in 10 children. Characteristic radiographic changes were seen in all the 8 children who underwent this examination. All children responded dramatically to treatment with oral Vitamin C. Conclusions: Awareness of clinical and radiographic signs of scurvy allows early diagnosis and treatment of scurvy. Dermatological manifestations are the most noticeable and helpful clues to the diagnosis of scurvy.